Particulate Matter, Ambient Air Pollution, and Respiratory Disease in Egypt - Heger, Martin; Zens, Gregor; Meisner, Craig (World Bank, Washington, DC, 2021)
Air pollution is known to be a risk factor for personal health and an important determinant of various diseases. Numerous studies exist that examine the effects of an increase in air pollution on the risk of disease and mortality from cardiovascular and cardiopulmonary causes. One possible way to quantify air pollution is to measure the concentration of particles with a specific diameter between 2.5 and 10 micrometers are referred to as (PM10).The authors assess the effects of air pollutants (PM10) on hospital admissions for respiratory diseases in Egypt in 2016. They use a retrospective design and employ a generalized additive model (GAM) to conduct our analysis. Daily hospital admission data for Chronic Obstructive Pulmonary Disease (COPD) and chronic bronchitis were collected from specialized chest hospitals and matched to air pollution data. The results suggest that the concentration of PM10 in the air is an important predictor of respiratory disease. The authors find that a 10 μg/